2008
DOI: 10.1007/s00125-008-1207-5
|View full text |Cite
|
Sign up to set email alerts
|

Absence of telomere shortening and oxidative DNA damage in the young adult offspring of women with pre-gestational type 1 diabetes

Abstract: Aims/hypothesis The offspring of mothers with pre-gestational type 1 diabetes (PGDM) may be at increased risk of glucose intolerance and cardiovascular disease in childhood. The underlying causes of these observations, and whether they persist into adulthood, are unknown. The aim of the present study was to test the hypothesis that fetal chromosomal telomere oxidative DNA damage resulting from maternal PGDM programmes the offspring towards a senescent phenotype that is detectable in young adulthood. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…As with the telomere data, the lack of difference in this study in hs‐CRP and sICAM‐1 concentrations could reflect the good glycaemic control in the diabetes populations [24]. We and others have previously shown that the young adult offspring of mothers with Type 1 diabetes do have elevated plasma sICAM‐1 levels, although they do not differ in venous nucleated blood cell telomere length, glucose tolerance, insulin sensitivity or nuclear magnetic resonance lipoprotein profiles [25].…”
Section: Discussionmentioning
confidence: 65%
“…As with the telomere data, the lack of difference in this study in hs‐CRP and sICAM‐1 concentrations could reflect the good glycaemic control in the diabetes populations [24]. We and others have previously shown that the young adult offspring of mothers with Type 1 diabetes do have elevated plasma sICAM‐1 levels, although they do not differ in venous nucleated blood cell telomere length, glucose tolerance, insulin sensitivity or nuclear magnetic resonance lipoprotein profiles [25].…”
Section: Discussionmentioning
confidence: 65%
“…Fifty per group gives us 80% power to see an odds ratio of 3.2 for top vs. bottom quartile, lower than the hazard ratio of 3.5 seen in previous studies of telomere length and cancer [37]. Several studies of this size looking at telomere length and reproductive outcomes have been published[22,30,32]…”
Section: Methodsmentioning
confidence: 97%
“…In addition, telomere length has been associated with oxidative stress, [16,27] and markers of oxidative stress are raised in pre-eclampsia[28] A recent article found lower telomere length in the placentas of women with pre-eclampsia and intrauterine growth retardation[29] We are unaware of other previous studies of telomere length in pre-eclampsia and gestational diabetes. For studies related to reproductive outcomes, no difference in telomere lengths was found in young adults whose mothers had pre-gestational type 1 diabetes[30], while another study of newborns did not find statistically significant differences in telomere lengths between newborns whose mothers had pre-eclampsia, hypertension, or diabetes[31]. However, these studies dealt with the child rather than the mothers.…”
Section: Introductionmentioning
confidence: 99%
“… demonstrated that the very strong associations between telomere length and chronic obstructive pulmonary disease and lung function indices were reduced to almost insignificance after adjusting for age, gender, smoking habits, body mass index and other lifestyle factors. Risk of diabetes has also been examined; the combined evidence does not suggest a strong association with telomere length , although it might be predictive of late complications of diabetes .…”
Section: Telomere Length As a Biomarkermentioning
confidence: 99%